THE INFLUENCE OF JOB SATISFACTION AND PERCEIVED AVAILABILITY OF JOB ALTERNATIVE ON TURNOVER INTENTION STUDY CASE AT PT. HASJRAT ABADI MANADO TENDEAN - Mosez, Taroreh Galileo; Lapian, Joice .; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract: One of the worker’s behavior is turnover intentions that will culminate in a decision to leave his job. Turnover is a tendency of employee to quit their job.This research aims to analyze the job satisfaction and job alternative have influence on employee turnover partially and simultaneously. Type of this research is descriptive with quantitative approach and Multiple Regression used as the measurement tool. The sample size of this research is a total of 100 employee of PT. Hasjrat Abadi Manado and were distributed to respondent through questionnaire.The result for the research says that Job Satisfaction, Perceived availability of job alternative significant influence on Turnover Intention simultaneously, Job Satisfaction has no significant influence toward Turnover Intention in PT. Hasjrat Abadi Manado partially, and Perceived availability of job alternative behavior has significant influence toward Turnover Intention in PT. Hasjrat Abadi Manado partially. The suggestion that can be given from this study is that the company should provide the right prevention solution to prevent undesirable things that may be happened. Keywords: job satisfaction, job alternative, turnover intention